Fast and stable electrical discharge machining (EDM). (May 2016) - Wu, Jianyang; Zhou, Ming; Xu, Xiaoyi; Yang, Jianwei; Zeng, Xiangwei; Xu, Donghui
Abstract: In order to improve EDM performances, the most important issue is to develop a highly stable control system. As a serious defect in EDM adaptive control system by minimum-variance control law, the occasional instability deterred its full applications in industries. This paper focuses on stabilizing EDM process by establishing a new minimum-variance and pole-placement coupled control law. Based on real-time estimation of EDM process model parameters, this adaptive control system directly controls electrode discharging cycle not only to follow a specified gap state for fast machining but also to track the dynamical response of a reference model for stabilizing EDM process. Confirmation experiment demonstrates that this control system can timely adjust electrode discharging cycle in terms of different machining situations quantified as a series of varied gap states to maintain a stable and fast fabrication. The adaptive control system by this newly developed control law exhibits its superior machining ability and capability of stabilizing sparking process to those of the adaptive control system by minimum-variance control law. The adaptive system has actually theoretically and technically solved the stability issue puzzled EDM circle for decades. Highlights: EDM process is in nonlinear stochastic dynamics, easily into unstable process. Severe electrode fluctuations occur when adopting adaptive minimum variance strategy. A coupled control strategy is proposed considering both machining rate and stability. Experiments confirm the superior performances of the new coupled control strategy. The newly developed control system has been proved working well in severe conditions.